CD105 expression in bone marrow cells and peripheral blood lymphocytes in children with cancer - Styczyński, Jan; Piątkowska, Magdalena; Dębski, Robert; Krenska, Anna; Górnicka, Hanna; Hulek, Elżbieta; Kubicka, Małgorzata; Kuryło-Rafińska, Beata; Kołodziej, Beata (Contemporary Oncology/Współczesna Onkologia, 2007)
Background: Bone marrow contains hematopoietic stem cells and mesenchymal stem cells, which are best characterized by expression of CD105, CD90, CD44 and CD29 antigens. Aim: Analysis of CD105 expression in bone marrow and peripheral blood cells of children with cancer in various clinical stages. Material and methods: A total number of 84 children entered the study, including: patients with acute lymphoblastic leukemia at diagnosis and in remission; patients with solid tumors undergoing transplantation of autologous hematopoietic stem cell transplantation; and healthy controls. Expression of CD105 and CD34 was analyzed in all cases. Results: Higher percentage of CD105+ cells was found in bone marrow than in peripheral blood: in healthy children, during chemotherapy and after stimulation with G-CSF. Children with acute lymphoblastic leukemia at diagnosis had higher expression of CD105+ cells than healthy controls, however this expression decreased during chemotherapy. Patients with solid tumors, after G-CSF priming had an increase of CD105 in bone marrow but not in peripheral blood. After hematopoietic stem cell transplantation, an increase of bone marrow CD105 was observed. There was no correlation between expression of CD105 and CD34 cells. Conclusions: Expression of CD105 in bone marrow and peripheral blood is probably related to overlapping of expression of different cell populations. Various clinical stages, such as chemotherapy, G-CSF administration and diagnosis of acute lymphoblastic leukemia might lead to an increase of CD105+ cells in children.